2022
DOI: 10.3390/foods11020219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Endogenous Factors of Food Matrices on Avidin—Biotin Immunoassays for the Detection of Bacitracin and Colistin in Food

Abstract: (Strept)avidin–biotin technology is frequently used in immunoassay systems to improve their analytical properties. It is known from clinical practice that many (strept)avidin–biotin-based tests provide false results when analyzing patient samples with a high content of endogenous biotin. No specific investigation has been carried out regarding possible interferences from avidin (AVI) and biotin (B7) contained in food matrices in (strept)avidin–biotin-based immunoanalytical systems for food safety. Two kinds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Insulin is well protected from proteolytic degradation (triggered by trypsin and chymotrypsin) when encapsulated with these enzyme inhibitors, as compared with unadulterated insulin solutions, in vitro [110]. Bacitracin, a cyclic polypeptide antibiotic with a molecular weight of 1422.7 Da, is another enzyme inhibitor that effectively inhibits various proteases, including trypsin, pepsin and aminopeptidase [111]. An in vitro study has reported that bacitracin, camostat mesilate and sodium glycocholate decrease insulin degradation in rat large intestinal homogenate [112].…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…Insulin is well protected from proteolytic degradation (triggered by trypsin and chymotrypsin) when encapsulated with these enzyme inhibitors, as compared with unadulterated insulin solutions, in vitro [110]. Bacitracin, a cyclic polypeptide antibiotic with a molecular weight of 1422.7 Da, is another enzyme inhibitor that effectively inhibits various proteases, including trypsin, pepsin and aminopeptidase [111]. An in vitro study has reported that bacitracin, camostat mesilate and sodium glycocholate decrease insulin degradation in rat large intestinal homogenate [112].…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…Assessing the matrix interference on the assay sensitivity is thus an important issue in the development of methods. Burkin et al [ 3 ] firstly evaluated the influence of avidin (AVI) and biotin (B7) contained in food matrices on two kinds of (Strept)avidin–biotin-based enzyme-linked immunosorbent assays (ELISAs) for bacitracin (BT) and colistin (COL) determination, with simultaneous assessment of extraneous AVI/B7 and AVI/B7 from different matrices (egg, infant milk formulas enriched with B7, and chicken and beef liver). Summarizing the experience of the present study, it is recommended to avoid immunoassays based on avidin–biotin interactions when analyzing samples containing these endogenous factors or enriched with B7.…”
mentioning
confidence: 99%